Landscape planning-addressed regional-scale mapping of geolithological units: an example from Southern Italy - Marcello Schiattarella; Paolo Giannandrea; Giuseppe Corrado; Dario Gioia (Journal of Maps)
A 1:100,000-scale geolithological map has been prepared for the Basilicata region (Southern Italy) through an extensive review of official geological maps integrated by photogeological analyzes and field surveys. A double-key legend allows discriminating both lithological and technical properties of the rock bodies. This map together with the main relief-scale morpho-structural features, permitted us a subsequent recognition of the different landscape domains of the region, which have been summarized in a derived map. The two products represent an effective basis for landscape planning purposes and a key tool to highlight the spatial distribution of the ‘geological landscape’ in a sector characterized by a high degree of geodiversity.